2020
DOI: 10.1186/s13063-019-3827-0
|View full text |Cite
|
Sign up to set email alerts
|

Protocol for a cluster randomised controlled trial to determine the effectiveness and cost-effectiveness of independent pharmacist prescribing in care homes: the CHIPPS study

Abstract: Background: Prescribing, monitoring and administration of medicines in care homes could be improved. Research has identified the need for one person to assume overall responsibility for the management of medicines within each care home. and shown that a pharmacist independent prescriber service is feasible in this context. Aims and objectives: To conduct a cluster randomised controlled trial to determine the effectiveness and costeffectiveness of a pharmacist-independent prescribing service in care homes compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

6
2

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 16 publications
0
21
0
Order By: Relevance
“… 16 - 19 Considering pharmacists' proven benefit in the primary care setting, a randomized controlled trial in the United Kingdom is underway to evaluate the effectiveness and cost-effectiveness of a pharmacist-independent prescribing service compared to usual general practitioner–led care in the home care setting. 20 Although psychiatric pharmacists do not currently have independent prescriptive authority outside of collaborative practice agreements, they are able to assist with medication management follow-up appointments, particularly once initial diagnoses and treatment plans have been developed by a consulting psychiatrist. As such, expanding partnerships to board-certified psychiatric pharmacists with expertise in psychiatric medication management could help address the shortage of psychiatric specialty care support in HBPC settings.…”
Section: Discussionmentioning
confidence: 99%
“… 16 - 19 Considering pharmacists' proven benefit in the primary care setting, a randomized controlled trial in the United Kingdom is underway to evaluate the effectiveness and cost-effectiveness of a pharmacist-independent prescribing service compared to usual general practitioner–led care in the home care setting. 20 Although psychiatric pharmacists do not currently have independent prescriptive authority outside of collaborative practice agreements, they are able to assist with medication management follow-up appointments, particularly once initial diagnoses and treatment plans have been developed by a consulting psychiatrist. As such, expanding partnerships to board-certified psychiatric pharmacists with expertise in psychiatric medication management could help address the shortage of psychiatric specialty care support in HBPC settings.…”
Section: Discussionmentioning
confidence: 99%
“…The definitive RCT is evaluating the efficacy and efficiency of implementing and delivering a PIP service and comparing outcomes for care home residents who receive the PIP service with outcomes for residents who continue to receive usual care [13]. In total 44 GP/PIP/care home groups (subsequently referred to as triads) and 880 patients will be included in four geographical areas of East Anglia, Leeds, North East Scotland and Northern Ireland.…”
Section: Causal Assumptionsmentioning
confidence: 99%
“…Requests for access to the data will be considered, and approved in writing where appropriate, after formal application to the Trial Management Committee/Programme Steering Committee [13]. Considerations for approving access are documented in the Project Management Group/ Programme Steering Committee Terms of Reference [13].…”
Section: Supplementary Informationmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been suggested that errors would be reduced if a single person took on overall responsibility for the medicines management in care homes. Our team proposed this should be an independent prescribing pharmacist (PIP) linked to the care home, and are undertaking a programme of work which has identified logistical and professional barriers to a PIP care home service, and devised solutions to address them 10 , devised a training programme for the PIPs to ensure they have the requisite competencies to deliver the service, and identified provisional measures of outcome 11 in preparation for a definitive cluster randomised controlled trial (RCT) to compare the outcomes from the PIP service with usual care. A mixed methods non-randomised feasibility study 12 confirmed the acceptability and feasibility of the processes for participant identification, recruitment and informed consent.…”
Section: Introductionmentioning
confidence: 99%